1983
DOI: 10.1289/ehp.83493
|View full text |Cite
|
Sign up to set email alerts
|

Some historical aspects of N-aryl carcinogens and their metabolic activation.

Abstract: This limited review of the early studies on the activation of the N-aryl carcinogens was written to provide a background for the current research to be presented at this conference on carcinogenesis by N-aryl compounds. Since the work of the past 10 years is too recent to be judged in a historical sense and because those data are much better known by current investigators, this review is generally limited to data up to 1972.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(18 citation statements)
references
References 59 publications
(30 reference statements)
0
18
0
Order By: Relevance
“…This observation, plus DAB's high molar extinction coefficient at visible wavelengths (which facilitated its study in the days preceding radiolabeled compounds), resulted in a number of investigations being conducted with this aminoazo dye (2). The first step in the metabolic activation of DAB is a cytochrome P-450-catalyzed oxidative N-demethylation to N-methyl-4-aminoazobenzene (MAB) (2,77).…”
Section: Benzidinementioning
confidence: 99%
See 2 more Smart Citations
“…This observation, plus DAB's high molar extinction coefficient at visible wavelengths (which facilitated its study in the days preceding radiolabeled compounds), resulted in a number of investigations being conducted with this aminoazo dye (2). The first step in the metabolic activation of DAB is a cytochrome P-450-catalyzed oxidative N-demethylation to N-methyl-4-aminoazobenzene (MAB) (2,77).…”
Section: Benzidinementioning
confidence: 99%
“…This observation, plus DAB's high molar extinction coefficient at visible wavelengths (which facilitated its study in the days preceding radiolabeled compounds), resulted in a number of investigations being conducted with this aminoazo dye (2). The first step in the metabolic activation of DAB is a cytochrome P-450-catalyzed oxidative N-demethylation to N-methyl-4-aminoazobenzene (MAB) (2,77). Since a second N-demethylation, which yields 4-aminoazobenzene (AB), generally results in a decrease in carcinogenicity, most studies have concentrated on MAB, which is further activated by FMOcatalyzed N-oxidation to N-hydroxy-MAB and then is converted to an ultimate carcinogen through PAPS-dependent formation of N-sulfonyloxy-MAB.…”
Section: Benzidinementioning
confidence: 99%
See 1 more Smart Citation
“…1) In contrast, these N-arylacylamides are deacylated to the corresponding arylamines, and this process also contributes the toxicity of N-arylacylamides. [2][3][4][5] 2-Acetylaminofluorene and 2-formylaminofluorene, typical carcinogenic aromatic acylamines, were reported to be deacylated in animal bodies.…”
Section: Introductionmentioning
confidence: 99%
“…These arylamines are also acylated to N-arylacetamide and N-arylformamide, which are themselves toxic. Several reports have indicated that arylacetamides and arylformamides are further activated by hydroxylation to the corresponding hydroxamic acids, and N-hydroxy-2-acetylaminofluorene is further activated by sulfate conjugation in mammalian species (Miller and Miller, 1983). In contrast, these N-arylacylamides are deacylated to the corresponding arylamines, and this process also contributes to the toxicity of N-arylacylamides (Glinsukon et al, 1980;Aune et al, 1985;Land et al, 1989).…”
mentioning
confidence: 99%